2019
DOI: 10.3390/jcm8111972
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies in Male Patients under Treatment for Substance Use Disorders and/or Severe Mental Illness: Influence in Clinical Course at One-Year Follow-Up

Abstract: Coping strategies have an impact on substance use disorders (SUD), relapses, and clinical variables, but knowledge on this area is scarce. We explored the coping strategies used during treatment in patients with dual diagnosis (DD), SUD, and severe mental illness (SMI), and the relation with clinical course and relapses at one-year follow-up. A sample of 223 patients was divided into three groups depending on diagnosis: DD (N = 80; SUD with comorbid schizophrenia or major depressive disorder), SUD only (N = 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 51 publications
4
19
1
1
Order By: Relevance
“…Consistent with previous findings, we did not find any differences between groups in the age of SUD onset between groups (30). The SUD + MDD patients showed higher rates of medical disorder comorbidity (30,37,59) and more suicide attempts (26,28,30,32,37,59,60). In the current research, the SUD + MDD patients reported more personal psychiatric history than the SUD ones (39,61,62), which is in line with a recent study on SUD + MDD patients with lower mental health component compared with the SUD ones (30).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous findings, we did not find any differences between groups in the age of SUD onset between groups (30). The SUD + MDD patients showed higher rates of medical disorder comorbidity (30,37,59) and more suicide attempts (26,28,30,32,37,59,60). In the current research, the SUD + MDD patients reported more personal psychiatric history than the SUD ones (39,61,62), which is in line with a recent study on SUD + MDD patients with lower mental health component compared with the SUD ones (30).…”
Section: Discussionsupporting
confidence: 91%
“…Relapses at 3 months were related to two different quality of life dimensions depending on whether the patient was asymptomatic SUD + MDD or a patient with SUD. Thus, in patients with SUD, worse physical function (limitations in daily physical activities) was associated with a greater probability of having relapses throughout the year of follow-up (3, 6, and 12 months); these data are in agreement with published studies that associate the use of maladaptive coping strategies with a higher probability of relapse in patients with dual disorders [ 6 , 51 ]. Future studies should deepen this relationship and investigate whether the presence of physical problems in SUD reduces the patient’s motivation to maintain abstinence or whether consumption works as a strategy to cope with these daily limitations.…”
Section: Discussionsupporting
confidence: 89%
“…Both from the field of research and from clinical practice, different indicators of success of the treatment or recovery of the patient are currently being investigated, beyond the simple reduction of psychiatric symptoms and withdrawal from substance use [ 4 , 5 ]. There are different published studies that explain the relevance of certain variables that function as indicators of the patient’s prognosis [ 6 , 7 , 8 ], among which is quality of life [ 8 , 9 ]. Undoubtedly, having indicators at the start of treatment that report a poor clinical evolution can be key for adjusting the intervention to the specific needs of each patient [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accessible mental health services for all patients, with the capacity to promote the rapid reintegration of those who miss appointments also contributes to a better outcome. In addition, simplified therapeutic regimens, considering the introduction of long-acting injectable antipsychotic, contribute to treatment compliance [31,32]. Since the side effects of antipsychotics are sometimes responsible for non-adherence to the treatment, the clinician must monitor its appearance and not devalue their burden on the patient.…”
Section: Discussionmentioning
confidence: 99%